Factor Analysis of Collaboration Between Parents and Teachers - Nikmaturrohmah, Nikmaturrohmah; Rahmadani, Ni Kadek Aris (LP. Ma'arif Janggan Magetan, 2025)
Collaboration between parents and teachers is key to optimizing the success of children's education, considering that education takes place both at home and at school. This study aims to describe the supporting and inhibiting factors of collaboration between teachers and parents at Ar-Rohmah KB Playgroup. The approach used in this study is descriptive qualitative with data collection techniques through observation, interviews and documentation. The results showed that there are three main factors in realizing collaboration between teachers and parents, namely effective communication, parental involvement at home, and field trip activities. In addition, there are supporting factors for collaboration, including the communication system and trust between parents and teachers. On the other hand, the inhibiting factors include the limited time of parents who are busy with work and sudden changes in the collaboration schedule. This research provides novelty by highlighting the importance of structural approaches in collaboration between teachers and parents. The practical impact of this research is to provide recommendations for educational institutions to strengthen such collaboration, in order to support optimal early childhood development.